Crime and criminology: an introduction to theory - Eisler, Lauren D. (Oxford University Press, 2023)
"The fourth edition of Crime and Criminology is a concise, comprehensive overview of criminological theory. By relating classical and contemporary theories to current criminological concerns through case studies and examples--such as racial profiling, sex trafficking, domestic violence, and cybercrime--the fourth edition is an up-to-date and remarkably accessible introduction to the study of theory in Canadian criminology."--